Beyond the Screen: Unveiling the Impact of Digital Literacy on Vocational Internship Performance in the Industry 4.0 Era - Siti Sahara; Yoyoh Jubaedah; Tutin Aryanti; Iwa Kuntadi; Isma Isma Widiaty (Universitas Sultan Ageng Tirtayasa, 2025)
The advancement of digital technology in the Industry 4.0 era has transformed the paradigm of vocational education, necessitating that students acquire digital literacy as an essential ability. Digital literacy encompasses not just the technical proficiency in utilizing software or programs but also entails a critical understanding of ethics, data security, and professional communication skills. This study seeks to examine the impact of digital literacy on the internship performance of vocational students. The research design employs a descriptive-correlational quantitative methodology with simple linear regression analysis. Data was collected via a survey of 50 students enrolled in the Mechanical Engineering Education and Electrical Engineering Education programs at Jakarta State University, who were participating in internships in diverse manufacturing, automotive, and information technology firms. The questionnaire has undergone validation and reliability testing and is augmented by comprehensive interviews with internship supervisors to enhance the findings. The study indicates that digital literacy significantly influences internship performance, evidenced by a significance value of 0.031 (< 0.05) and an F-statistic of 4.946 (> F-table 1.624). Digital literacy has been demonstrated to improve students' technical, communicative, management, and collaborative abilities, while also augmenting their preparedness for employment in a digitized industrial landscape. This discovery affirms that digital literacy must be established as a core ability inside the vocational education curriculum. This research is unusual in its explicit emphasis on connecting digital literacy with internship performance in the industrial sector through a quantitative methodology, surpassing prior studies that predominantly concentrated on the academic context. This research underscores the necessity to enhance the curriculum, fortify business ties, and develop digital training programs to adequately educate vocational students for the challenges of the workforce.